Lithium aluminate modified graphite negative electrode material, preparation method thereof and graphite negative electrode plate
By covering polydopamine on the graphite surface and forming a lithium aluminate shell layer, the graphite negative electrode material is modified, and the problem of poor power performance of graphite negative electrode material is solved, and the high magnification and fast charging performance of graphite negative electrode material is achieved, which significantly improves cycle stability sex.
Patent Information
- Application Number
- CN202411550208.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-07
AI Technical Summary
Graphite negative electrode materials have high surface activity, unstable solid electrolyte interfaces and capacity attenuation problems under large currents in lithium-ion batteries, resulting in poor power performance and limiting applications of fast charging and high magnification.
By coating polydopamine on the graphite surface and reacting with aluminum salt and lithium-containing compound, a lithium aluminate shell layer is formed, and the graphite negative electrode material is modified to prepare a graphite negative electrode sheet with excellent rate performance and cycle stability.
The graphite negative electrode material modified by lithium aluminate can protect the graphite material from corrosion by electrolyte, reduce the diffusion energy barrier of lithium ions, stabilize the solid electrolyte interface, promote the transmission of lithium ions, and significantly improve the power performance and cycling stability of the graphite negative electrode.
Smart Images

Figure CN119400833A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphite negative electrodes, and in particular to a lithium aluminate-modified graphite negative electrode material and a preparation method thereof, and a graphite negative electrode pole piece. Background Art
[0002] Graphite material is the most commonly used negative electrode material for lithium-ion batteries, accounting for more than 96% of negative electrode materials. Compared with other negative electrode materials, graphite has the advantages of high theoretical capacity, suitable lithiation / delithiation potential, abundant resources and low cost. However, graphite also has problems such as high surface activity, unstable solid electrolyte interface (SEI) and capacity decay under high current. With the rapid growth of the global electric vehicle market, the poor power performance of graphite materials has become a major obstacle, and the development of high-rate lithium-ion batteries with fast charging capabilities has become an inevitable trend.
[0003] In order to achieve high-performance graphite anode with fast charging, the design of electrolyte and the modification of graphite play an important role. On the one hand, various additives are introduced into the electrolyte to optimize the components of SEI and thus improve the ionic conductivity at the interface. However, it should be pointed out that the cost of additives is high, and about 60% of the additives will remain in the electrolyte solution. In addition, the continuous consumption of additives will lead to a continuous increase in resistance during the cycle. On the other hand, redesigning the graphite structure is also widely used. In the production of commercial graphite, graphite is usually subjected to secondary granulation and spheroidization. The kinetics are optimized by exposing more active sites and shortening the ion transport path, but this preparation requires a lot of energy consumption. Therefore, it is of great significance to study a lithium aluminate-modified graphite anode material and its preparation method, and make it into a graphite anode pole piece to achieve fast charging. Summary of the invention
[0004] The purpose of the present invention is to provide a lithium aluminate modified graphite negative electrode material and a preparation method thereof and a graphite negative electrode pole piece, so as to solve the technical problem of poor power performance of graphite negative electrodes in the prior art.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a lithium aluminate modified graphite negative electrode material, comprising the following steps:
[0007] (1) mixing a dopamine hydrochloride solution and graphite particles, adjusting the pH value to 7.5-8.5, and then drying to obtain polydopamine-coated graphite;
[0008] (2) The polydopamine-coated graphite, the aluminum salt solution and the lithium-containing compound solution are mixed and then dried and solid-phase reacted in sequence to obtain a lithium aluminate-modified graphite negative electrode material.
[0009] Preferably, in step (1), the mass concentration of the dopamine hydrochloride solution is 0.1-1.0%; and the mass ratio of the dopamine hydrochloride solution to the graphite particles is 1-5:1.
[0010] Preferably, in step (2), the mass concentration of the aluminum salt solution is 0.5-2%; and the mass concentration of the lithium-containing compound solution is 0.1-1%.
[0011] Preferably, in step (2), the aluminum salt in the aluminum salt solution comprises one or more of aluminum isopropoxide, aluminum nitrate, aluminum chloride, aluminum sulfate, aluminum silicate, aluminum fluoride and aluminum phosphate; and the lithium-containing compound in the lithium-containing compound solution comprises one or more of lithium oxalate, lithium hydroxide, lithium carbonate, lithium nitrate, lithium chloride and lithium sulfate.
[0012] Preferably, in step (2), the mass ratio of the polydopamine-coated graphite, the aluminum salt solution and the lithium-containing compound solution is 1:2 to 5:1.
[0013] Preferably, in step (2), the drying temperature is 60-80°C.
[0014] Preferably, in step (2), the temperature of the solid phase reaction is 700-900° C., and the time of the solid phase reaction is 2-4 hours.
[0015] The present invention provides a lithium aluminate-modified graphite negative electrode material obtained by the preparation method of the lithium aluminate-modified graphite negative electrode material described above, wherein the lithium aluminate-modified graphite negative electrode material consists of a graphite particle core and a lithium aluminate shell layer, wherein the thickness of the lithium aluminate shell layer is 5 to 50 nm.
[0016] Preferably, the mass content of lithium aluminate in the lithium aluminate-modified graphite negative electrode material is 1-5%.
[0017] The present invention provides a graphite negative electrode plate, which is made of the above-mentioned lithium aluminate modified graphite negative electrode material, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber.
[0018] Beneficial effects of the present invention:
[0019] (1) The present invention first coats the graphite surface with polydopamine, and the obtained polydopamine template forms a strong interaction with aluminum ions to evenly anchor the aluminum ions on the graphite surface, and further in situ grows a lithium aluminate shell on the graphite surface through a high-temperature solid phase reaction. Lithium aluminate has strong mechanical properties and high thermal stability. On the one hand, it can protect the graphite material from corrosion by the electrolyte, and on the other hand, it can reduce the diffusion energy barrier of lithium ions on the graphite surface, limit the volume expansion of the graphite particles, stabilize the SEI film on the graphite surface, thereby promoting the transmission of lithium ions, and suppressing the phenomenon of continuous rupture and reformation of the SEI film on the graphite surface.
[0020] (2) The graphite negative electrode sheet prepared by the present invention has excellent rate performance and cycle stability, and has important development and utilization value.
[0021] (3) The preparation method provided by the present invention has simple process, low cost, non-toxicity and harmlessness, and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is a SEM image of the graphite particles used in the comparative example;
[0023] Figure 2 This is a SEM image of the lithium aluminate modified graphite negative electrode material prepared in Example 1;
[0024] Figure 3 TEM image of graphite particles used in the comparative example;
[0025] Figure 4 TEM image of the lithium aluminate modified graphite negative electrode material prepared in Example 1;
[0026] Figure 5 It is a performance comparison diagram of the first charge and discharge curves of the half-cell of the comparative example and embodiment 1;
[0027] Figure 6 It is a performance comparison diagram of the first charge and discharge curves of a full battery assembled with the graphite particles of the comparative example and the lithium aluminate modified graphite negative electrode material of Example 1;
[0028] Figure 7 It is a comparison chart of the long-term cycle performance of the full battery assembled with the graphite particles of the comparative example and the lithium aluminate modified graphite negative electrode material of Example 1;
[0029] Figure 8 This is a comparison chart of the rate charge and discharge performance of a full battery assembled with the graphite particles of the comparative example and the lithium aluminate modified graphite negative electrode material of Example 1. DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing a lithium aluminate modified graphite negative electrode material, comprising the following steps:
[0031] (1) mixing a dopamine hydrochloride solution and graphite particles, adjusting the pH value to 7.5-8.5, and then drying to obtain polydopamine-coated graphite;
[0032] (2) The polydopamine-coated graphite, the aluminum salt solution and the lithium-containing compound solution are mixed and then dried and solid-phase reacted in sequence to obtain a lithium aluminate-modified graphite negative electrode material.
[0033] In the present invention, the particle size of the graphite particles is 5 to 20 μm, preferably 7 to 15 μm, and the graphite particles are preferably natural flake graphite particles or artificial graphite particles.
[0034] The particle size of graphite cannot be too large, and lithium aluminate does not significantly improve the power performance of modified large-particle graphite negative electrode materials.
[0035] In the present invention, in the step (1), the adjusted pH value is preferably 8.0; the drying temperature is 60 to 80°C, preferably 65 to 75°C, and more preferably 70°C.
[0036] In the present invention, in the step (1), the mass concentration of the dopamine hydrochloride solution is 0.1-1.0%, preferably 0.3-0.8%, and more preferably 0.5-0.6%; the mass ratio of the dopamine hydrochloride solution to the graphite particles is 1-5:1, preferably 2-4:1, and more preferably 3:1.
[0037] In the present invention, the dopamine hydrochloride solution is preferably prepared by using dopamine hydrochloride and water.
[0038] In the present invention, in step (2), the mass concentration of the aluminum salt solution is 0.5-2%, preferably 0.8-1.5%, and more preferably 1.0-1.3%; the mass concentration of the lithium compound solution is 0.1-1%, preferably 0.3-0.7%, and more preferably 0.5-0.6%.
[0039] In the present invention, in the step (2), the aluminum salt in the aluminum salt solution comprises one or more of aluminum isopropoxide, aluminum nitrate, aluminum chloride, aluminum sulfate, aluminum silicate, aluminum fluoride and aluminum phosphate, preferably one or more of aluminum isopropoxide, aluminum nitrate, aluminum fluoride and aluminum phosphate, and more preferably aluminum isopropoxide and / or aluminum phosphate; the lithium-containing compound in the lithium-containing compound solution comprises one or more of lithium oxalate, lithium hydroxide, lithium carbonate, lithium nitrate, lithium chloride and lithium sulfate, preferably one or more of lithium hydroxide, lithium carbonate, lithium nitrate and lithium chloride, and more preferably one or more of lithium hydroxide, lithium carbonate and lithium chloride.
[0040] In the present invention, the solvents in the aluminum salt solution and the lithium-containing compound solution are independently one or more of water, anhydrous ethanol, dimethylformamide, dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide, preferably one or more of water, anhydrous ethanol, dimethylformamide and dimethylacetamide, and more preferably water and / or anhydrous ethanol.
[0041] In the present invention, in step (2), the mass ratio of polydopamine-coated graphite, aluminum salt solution and lithium-containing compound solution is 1:2 to 5:1, preferably 1:3 to 4:1, and more preferably 1:3:1.
[0042] In the present invention, in the step (2), the drying temperature is 60 to 80°C, preferably 65 to 75°C, and more preferably 70°C.
[0043] In the present invention, in step (2), the temperature of the solid phase reaction is 700-900°C, preferably 750-850°C, and more preferably 800°C; the time of the solid phase reaction is 2-4h, preferably 2.5-3.5h, and more preferably 3h.
[0044] In the present invention, the solid phase reaction is carried out in a protective atmosphere, and the protective atmosphere is preferably an argon or helium atmosphere, and more preferably an argon atmosphere.
[0045] The present invention provides a lithium aluminate-modified graphite negative electrode material obtained by the preparation method of the lithium aluminate-modified graphite negative electrode material described above, wherein the lithium aluminate-modified graphite negative electrode material consists of a graphite particle core and a lithium aluminate shell layer, wherein the thickness of the lithium aluminate shell layer is 5 to 50 nm.
[0046] In the present invention, the mass content of lithium aluminate in the lithium aluminate-modified graphite negative electrode material is 1 to 5%, preferably 2 to 4%, and more preferably 3%.
[0047] The present invention provides a graphite negative electrode plate, which is made of the above-mentioned lithium aluminate modified graphite negative electrode material, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber.
[0048] In the present invention, the mass ratio of the lithium aluminate-modified graphite negative electrode material, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber is 94-98:1:1-3:1, preferably 95-97:1:2:1, and more preferably 96:1:2:1.
[0049] In the present invention, the preparation method of the graphite negative electrode sheet is: disperse the lithium aluminate modified graphite negative electrode material, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber in water to make a slurry, and then sequentially coat the slurry, dry it for the first time, press it, slice it and dry it for the second time to obtain the graphite negative electrode sheet.
[0050] In the present invention, the mass volume ratio of the lithium aluminate modified graphite negative electrode material and water is 1g:2~5mL, preferably 1g:3~4mL; the temperature of the first drying is 60~70℃, preferably 65℃, and the time of the first drying is 4~12h, preferably 6~10h, and more preferably 8h; the temperature of the second drying is 100~140℃, preferably 110~130℃, and more preferably 120℃; the time of the second drying is 12~20h, preferably 14~18h, and more preferably 16h.
[0051] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0052] Example 1
[0053] 1 g of natural flake graphite particles (particle size 7 μm) was added to 2 g of dopamine hydrochloride solution (made of dopamine hydrochloride and deionized water, with a mass concentration of 0.5%), and the pH value was adjusted to 8 after sufficient stirring. Finally, the mixture was dried at 70° C. until the solvent was completely evaporated to obtain polydopamine-coated graphite.
[0054] 0.5 g of aluminum isopropoxide was dissolved in 49.5 g of anhydrous ethanol, and the mixture was stirred for 12 h to obtain an aluminum isopropoxide solution with a mass concentration of 1%; 0.25 g of lithium hydroxide was dissolved in 49.75 g of anhydrous ethanol, and the mixture was stirred for 12 h to obtain a lithium hydroxide solution with a mass concentration of 0.5%.
[0055] 1 g of polydopamine-coated graphite, 3 g of aluminum isopropoxide solution and 1 g of lithium hydroxide solution were mixed evenly, and then dried at 70° C. until the solvent was completely evaporated, and the obtained powder was ground.
[0056] The ground powder was placed in an argon atmosphere, and then the temperature was raised to 800°C and kept for 3 hours for solid phase reaction to obtain a lithium aluminate-modified graphite negative electrode material, in which the mass content of lithium aluminate was 3% and the thickness of the lithium aluminate shell was about 50 nm.
[0057] The graphite negative electrode sheet was prepared by using the lithium aluminate modified graphite negative electrode material prepared above: 0.96g of lithium aluminate modified graphite negative electrode material, 0.01g of conductive carbon black, 0.02g of sodium carboxymethyl cellulose and 0.01g of styrene-butadiene rubber were dispersed in 3mL of deionized water to prepare a slurry, and then the slurry was coated and dried at 65°C for 8h, pressed and sliced, and then dried in a vacuum drying oven at 120°C for 16h to obtain a graphite negative electrode sheet. The above graphite negative electrode sheets were assembled into C2032 button batteries in a glove box.
[0058] Example 2
[0059] The difference from Example 1 is that the aluminum isopropoxide solution is replaced by aluminum nitrate solution, and other conditions are the same. The mass content of lithium aluminate in the obtained lithium aluminate-modified graphite negative electrode material is 3%, and the thickness of the lithium aluminate shell is about 50 nm.
[0060] Example 3
[0061] The difference from Example 1 is that the lithium hydroxide solution is replaced by a lithium carbonate solution, and other conditions are the same. The mass content of lithium aluminate in the obtained lithium aluminate-modified graphite negative electrode material is 3%, and the thickness of the lithium aluminate shell is about 50 nm.
[0062] Example 4
[0063] The difference from Example 1 is that the aluminum isopropoxide solution is replaced by an aluminum fluoride solution, and the lithium hydroxide solution is replaced by a lithium nitrate solution. Other conditions are the same. The mass content of lithium aluminate in the obtained lithium aluminate-modified graphite negative electrode material is 3%, and the thickness of the lithium aluminate shell is about 50 nm.
[0064] Example 5
[0065] The difference from Example 1 is that the aluminum isopropoxide solution is replaced by an aluminum phosphate solution, and other conditions are the same. The mass content of lithium aluminate in the obtained lithium aluminate-modified graphite negative electrode material is 3%, and the thickness of the lithium aluminate shell is about 50 nm.
[0066] Example 6
[0067] The difference from Example 1 is that the lithium hydroxide solution is replaced by a lithium chloride solution, and other conditions are the same. The mass content of lithium aluminate in the obtained lithium aluminate-modified graphite negative electrode material is 3%, and the thickness of the lithium aluminate shell is about 50 nm.
[0068] Example 7
[0069] The difference from Example 1 is that the lithium hydroxide solution is replaced by a lithium oxalate solution, and other conditions are the same. The mass content of lithium aluminate in the obtained lithium aluminate-modified graphite negative electrode material is 3%, and the thickness of the lithium aluminate shell is about 50 nm.
[0070] Comparative Example
[0071] Directly use graphite particles to prepare graphite negative electrode sheets: 0.96g of graphite particles, 0.01g of conductive carbon black, 0.02g of sodium carboxymethyl cellulose and 0.01g of styrene-butadiene rubber are dispersed in 3mL of deionized water to prepare slurry, and then the slurry is coated and dried at 65°C for 8h to obtain graphite negative electrode sheets, which are pressed and sliced and then dried in a vacuum drying oven at 120°C for 16h to obtain graphite negative electrode sheets. The above graphite negative electrode sheets are assembled into C2032 button batteries in a glove box.
[0072] The electrochemical performance of C2032 button cells assembled with the graphite negative electrode sheets prepared in the above Examples 1 to 7 and the comparative example was tested. All the cells were first charged for 3 cycles at 0.05C, and then charged at 0.2C and discharged at 0.5C for cycle performance testing. Rate performance testing was performed at different charge rates. The test results are shown in Table 1.
[0073] Table 1 Electrochemical performance test results of C2032 button batteries prepared in Examples 1 to 7 and Comparative Examples
[0074]
[0075]
[0076] It can be seen from Table 1 that compared with the comparative example, the first coulombic efficiency and capacity retention rate of Examples 1-6 obtained by the preparation method of the present invention are improved. It can be seen that the examples of the present application can significantly reduce the interface side reactions and improve the cycle stability by introducing the fast ion conductor shell layer. It is an important way to develop high-performance graphite negative electrode materials.
[0077] contrast Figure 1 and Figure 2 It was found that the lithium aluminate-modified graphite negative electrode material prepared in Example 1 was more uniform and smooth than the graphite particles of the comparative example, and the lithium aluminate particles were evenly distributed on the surface of the graphite particles.
[0078] contrast Figure 3 and Figure 4 It was found that compared with the exposed surface of the graphite particles in the comparative example, a lithium aluminate nanolayer with a thickness of about 50 nm was formed on the surface of the graphite particles in Example 1, which indicates that the lithium aluminate modification layer is uniformly coated on the surface of the graphite particles to form a continuous and uniform coating layer.
[0079] from Figure 5 It can be seen that the first charge and discharge capacity and long-term cycle performance of Example 1 in the half-cell are significantly improved compared with the comparative example, which indicates that the lithium aluminate-modified graphite negative electrode material has good electrochemical properties.
[0080] The lithium aluminate modified graphite negative electrode material prepared in Example 1 and the graphite particles in the comparative example were respectively assembled with the NCM622 positive electrode material, the PP separator, and the electrolyte (ingredients: 1 mol / L LiPF6; the volume ratio of EC:EMC:DMC was 1:1:1) to form a full battery. Figure 6 and Figure 7 It can be seen that the initial charge and discharge capacity and long-term cycle performance of the lithium aluminate-modified graphite negative electrode material prepared in Example 1 in the full battery are also significantly improved compared with the control example. After 700 cycles, the reversible capacity of the lithium aluminate-modified graphite negative electrode material in Example 1 is increased by 35%, which illustrates the feasibility of lithium aluminate-modified graphite negative electrode material in practical applications.
[0081] from Figure 8 It can be seen that the lithium aluminate modified graphite negative electrode material of Example 1 also has 117 mAh g under 5C and 10C high rate charging. -1 and 52mAh g -1 The capacity shows excellent fast charging capability. It can be foreseen that the performance can be further improved if the electrolyte composition is further optimized.
[0082] As can be seen from the above embodiments, the present invention provides a lithium aluminate modified graphite negative electrode material and a preparation method thereof and a graphite negative electrode sheet. The present invention first mixes a dopamine hydrochloride solution and graphite particles, and then adjusts the pH value to 7.5-8.5 to obtain polydopamine-coated graphite; then the polydopamine-coated graphite, aluminum salt solution and lithium-containing compound solution are mixed and then dried and solid-phase reacted in sequence to obtain a lithium aluminate modified graphite negative electrode material. In addition, the above lithium aluminate modified graphite negative electrode material is used to prepare a graphite negative electrode sheet. The lithium aluminate modified graphite negative electrode material of the present invention is composed of a graphite particle core and a lithium aluminate shell, wherein lithium aluminate has strong mechanical properties and high thermal stability. On the one hand, it can protect the graphite material from corrosion by the electrolyte, and on the other hand, it can reduce the diffusion energy barrier of lithium ions, limit the volume expansion of graphite particles, stabilize the SEI film on the graphite surface, and thus promote the transmission of lithium ions.
[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a lithium aluminate modified graphite negative electrode material, characterized in that: The steps include: (1) mixing a dopamine hydrochloride solution and graphite particles, adjusting the pH value to 7.5-8.5, and then drying to obtain polydopamine-coated graphite; (2) The polydopamine-coated graphite, the aluminum salt solution and the lithium-containing compound solution are mixed and then dried and solid-phase reacted in sequence to obtain a lithium aluminate-modified graphite negative electrode material.
2. The method for preparing the lithium aluminate modified graphite negative electrode material according to claim 1, characterized in that: In the step (1), the mass concentration of the dopamine hydrochloride solution is 0.1-1.0%; and the mass ratio of the dopamine hydrochloride solution to the graphite particles is 1-5:
1.
3. The method for preparing the lithium aluminate modified graphite negative electrode material according to claim 1 or 2, characterized in that: In the step (2), the mass concentration of the aluminum salt solution is 0.5-2%; the mass concentration of the lithium compound solution is 0.1-1%.
4. The method for preparing the lithium aluminate modified graphite negative electrode material according to claim 3, characterized in that: In the step (2), the aluminum salt in the aluminum salt solution includes one or more of aluminum isopropoxide, aluminum nitrate, aluminum chloride, aluminum sulfate, aluminum silicate, aluminum fluoride and aluminum phosphate; the lithium-containing compound in the lithium-containing compound solution includes one or more of lithium oxalate, lithium hydroxide, lithium carbonate, lithium nitrate, lithium chloride and lithium sulfate.
5. The method for preparing the lithium aluminate modified graphite negative electrode material according to claim 1, 2 or 4, characterized in that: In the step (2), the mass ratio of the polydopamine-coated graphite, the aluminum salt solution and the lithium-containing compound solution is 1:2 to 5:
1.
6. The method for preparing the lithium aluminate modified graphite negative electrode material according to claim 5, characterized in that: In the step (2), the drying temperature is 60 to 80°C.
7. The method for preparing the lithium aluminate modified graphite negative electrode material according to claim 4 or 6, characterized in that: In the step (2), the temperature of the solid phase reaction is 700 to 900° C., and the time of the solid phase reaction is 2 to 4 hours.
8. The lithium aluminate-modified graphite negative electrode material obtained by the method for preparing the lithium aluminate-modified graphite negative electrode material according to any one of claims 1 to 7, characterized in that: The lithium aluminate modified graphite negative electrode material consists of a graphite particle core and a lithium aluminate shell, wherein the thickness of the lithium aluminate shell is 5 to 50 nm.
9. The lithium aluminate modified graphite negative electrode material according to claim 8, characterized in that: The mass content of lithium aluminate in the lithium aluminate-modified graphite negative electrode material is 1-5%.
10. A graphite negative electrode plate, characterized in that: The graphite negative electrode plate is made of the lithium aluminate modified graphite negative electrode material according to claim 8 or 9, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber.
Citation Information
Cited By
Anode material based on organic-inorganic hybrid coating layer, preparation method and application
CN120497317A